Milton - Pattison, Mark, 1813-1884 (Salt Lake City, UT : Project Gutenberg, 2005)
"Milton" by Mark Pattison is a biographical account written in the late 19th century that explores the life and works of the renowned poet John Milton. The book delves into Milton's background, tracing his familial roots, education, and the influence of various experiences on his literary output. Pattison closely examines significant periods in Milton's life, detailing his early poetic endeavors, education, and later struggles as a prominent writer during turbulent times in England. The opening of "Milton" lays the groundwork for the exploration of the poet's formative years. It begins by discussing the obscurity surrounding the lives of poets in the 17th century, contrasting this with the wealth of personal details known about Milton. It highlights Milton's early education, his family's background, and the key influences in his life, including his experiences at school and university. The narrative emphasizes his fervent pursuit of knowledge and literature, setting the stage for the profound impact that these early experiences would have on his later works, such as "Paradise Lost." Pattison elaborates on Milton's character, indicating that his ambitions and intellectual rigor shaped the same profound and complex understanding of life and spirituality that would define his poetry. (This is an automatically generated summary.)
Release date is 2005-08-01
Produced by Charles Aldorondo, Tiffany Vergon, Marc D'Hooghe and the Online Distributed Proofreading Team
Keywords: Milton, John, 1608-1674